Privacy ontology support for E-commerce - Hecker, Michael; Dillon, Tharam S.; Chang, Elizabeth (IEEE, 2008)
Privacy is becoming increasingly important due to the advent of e-commerce. E-commerce applications frequently require customers to divulge many personal details about themselves that must be protected carefully in accordance with privacy principles and regulations. Here, the authors define a privacy ontology to support the provision of privacy and help derive the level of privacy associated with e-commerce transactions and applications. The privacy ontology provides a framework against which e-commerce sites can benchmark their privacy policies and implementations.